The Sierra Leone Trial to Introduce a Vaccine Against Ebola: An Evaluation of rVSV∆G-ZEBOV-GP Vaccine Tolerability and Safety During the West Africa Ebola Outbreak. (18th May 2018) - Samai, Mohamed; Seward, Jane F; Goldstein, Susan T; Mahon, Barbara E; Lisk, Durodami Radcliffe; Widdowson, Marc-Alain; Jalloh, Mohamed I; Schrag, Stephanie J; Idriss, Ayesha; Carter, Rosalind J; Dawson, Peter; Kargbo, S A S; et al.
Abstract: The West Africa Ebola epidemic stimulated rapid implementation of Ebola vaccine trials in the 3 highly affected countries. In Sierra Leone, we studied the recombinant vesicular stomatitis virus Ebola vaccine (rVSV∆G-ZEBOV-GP) safety and efficacy. The Sierra Leone Trial to Introduce a Vaccine against Ebola (STRIVE) was a randomized, unblinded Phase 2/3 trial with phased vaccine introduction, no placebo, and concurrent evaluation of vaccine safety and efficacy. Healthcare and frontline response workers in 5 districts were randomized to immediate or deferred (18–24 weeks later) vaccination and followed for 6 months postvaccination. We enrolled 8651 participants from April through August 2015; 7998 were vaccinated. No participants developed Ebola virus disease so an efficacy assessment was not possible. Overall, 132 (1.5%) participants experienced serious adverse events (SAEs); none were vaccine-related. In a detailed safety substudy (N = 436), vaccinated participants reported significantly more systemic adverse events (AEs) within 7 days than unvaccinated participants including fever higher than 38°C (20.5% vs 3.9%), headache (71.2% vs 22.1%), fatigue (50.7% vs 10.4%), and joint pain (31.7% vs 6.5%); most AEs were mild to moderate severity and resolved within 5 days. During days 5-28, vaccinated participants more commonly reported joint pain (17.0% vs 4.8%) and rash (7.8% vs 1.7%) ( P <.05 for both comparisons). Vaccinated participants also more commonly reported skin vesicles (2.0% vs 0%) and mouth ulcers (2.0% vs 0%) but only during days 8-14 ( P <.05 for both comparisons). Among almost 8000 high-risk workers vaccinated during the Sierra Leone Ebola epidemic, rVSV∆G-ZEBOV-GP was generally well tolerated with no vaccine-related SAEs. Reported joint pain, rash, skin vesicles, and mouth ulcers postvaccination are consistent with conditions associated with transient viral replication described among participants in other trials. Clinical Trials Registration: ClinicalTrials.gov [NCT02378753] and Pan African Clinical Trials Registry [PACTR201502001037220].